2004
DOI: 10.1021/ja045207x
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Structure of an Extended A-Tract:  [d(CGCAAATTTGCG)]2

Abstract: The crystal structure of [d(CGCAAATTTGCG)]2 has been determined to 1.5 A resolution, representing the first high-resolution structure of this DNA fragment. The ion interactions are novel. A spermine molecule replaces a Mg2+ observed in analogous structures. Unlike lower-resolution structures, the minor groove is narrow and the major groove lacks extra Watson-Crick hydrogen bonds. In addition, a monolayer of solvent sites, including a "spine of hydration", is visible in the minor groove. The crystal of [d(CGCAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(85 citation statements)
references
References 30 publications
7
78
0
Order By: Relevance
“…T n A n sequences do not contain a static bend in solution or in atomic structures, although T-A steps are highly flexible. Most studies show narrow minor grooves over AT-rich segments, but high-resolution structures of some AT sequences, particularly those containing one or more T-A steps, have been reported to display widened minor grooves (Mack et al 2001;Stefl et al 2004;Woods et al 2004). Fis binding to the F1 or F2 sequences containing central A n T n segments generate K d values of 0.2 nM and dissociation rates of 23 and 52 min, respectively (Figs.…”
Section: Fis Binding To Different Dna Sequencesmentioning
confidence: 98%
“…T n A n sequences do not contain a static bend in solution or in atomic structures, although T-A steps are highly flexible. Most studies show narrow minor grooves over AT-rich segments, but high-resolution structures of some AT sequences, particularly those containing one or more T-A steps, have been reported to display widened minor grooves (Mack et al 2001;Stefl et al 2004;Woods et al 2004). Fis binding to the F1 or F2 sequences containing central A n T n segments generate K d values of 0.2 nM and dissociation rates of 23 and 52 min, respectively (Figs.…”
Section: Fis Binding To Different Dna Sequencesmentioning
confidence: 98%
“…Poly(dA:dT) tracts are known to have a different structure, with a shorter helical structure and a narrow minor groove, which may contribute to their low propensity to form nucleosomes (32,119,129,143). In addition, data from crystallography studies suggest the presence of bifurcated hydrogen bonds between an A base and two T's on the opposite strand (32,119,201). However, the existence of these H bonds and their contribution to the structure of poly(dA:dT) remains unclear.…”
Section: At Content Is a Major Cis Factor Influencing Nucleosome Posimentioning
confidence: 99%
“…It has been suggested that the difference among these sites is at least partly due to differences in groove width [15][16][17]. Sites such as AATT, for example, have a more narrow groove than TTAA and are in a pre-binding conformation that is better suited to complex formation with unfused heterocyclic compounds such as those discussed above.…”
Section: Introductionmentioning
confidence: 99%